2007
DOI: 10.1007/s00787-007-0644-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective mutism

Abstract: About 84.51% of the schools returned forms covering 64,103 children. Five hundred and twenty six of these children were thought to have symptoms of SM by their teachers. After their DSM-IV based clinical evaluation by a child and adolescent psychiatrist, only 21 children were diagnosed as SM. Among the SM group, three were in the kindergarten, 15 were in the first grade and three were in the second grade. Twelve of the children were male and nine were female (male: female ratio is 1.3:1). In this cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…is study revealed many cases of selective mutism in infancy and suggested an improving trend in symptoms as such children advancing to higher grades. is nding supports the results of the study by Karakaya et al (2008), in which the enrollment rate was lower in elementary school than in kindergarten.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…is study revealed many cases of selective mutism in infancy and suggested an improving trend in symptoms as such children advancing to higher grades. is nding supports the results of the study by Karakaya et al (2008), in which the enrollment rate was lower in elementary school than in kindergarten.…”
Section: Discussionsupporting
confidence: 90%
“…In a survey conducted by Hisata et al (2016) in elementary schools in Kobe, and in a survey conducted by Kaji and Fujita (2017) in elementary schools in Amagasaki, the prevalence by grade level was evaluated based on DSM-5, and no decrease in prevalence was found at the higher grade levels. e prevalence by type of school was lower in elementary school than in kindergarten in a survey conducted by Karakaya, Sismanlar, Oc, Memik, Coskun, Agaoglu, and Yavuz (2008) and higher in lower secondary compared to an elementary school in a survey conducted by Muramoto (1983). erefore, we cannot conclude that the prevalence decreases at higher levels or stages of education.…”
Section: Introductionmentioning
confidence: 89%
“…Other researchers have examined the prevalence of SM in school-based samples by first asking teachers to identify extremely shy and reticent children in their classrooms, after which a psychological and/or psychiatric assessment was conducted to establish whether these children met the diagnostic criteria of the disorder. Using this approach, prevalence rates varied between 0.03 and 1.89% (Bergman et al 2002 : 0.71%; Elizur and Perednik 2003 : 0.76%; Karakaya et al 2008 : 0.03%; Kumpulainen et al 1998 : 1.89%; Sharkey and McNicholas 2012 : 0.18%), depending on sample characteristics, informants and assessment instruments, and exact diagnostic criteria employed to define the disorder.…”
Section: Selective Mutism (Sm)mentioning
confidence: 99%
“…It should be noted that some of the studies describe children who do not fulfill the criteria for selective mutism but are shy to an extent 'that they could not be regarded as clear non-cases' (Kopp and Gillberg 1997, 259). Of the schoolchildren in this study, 0.8-0.9% is found to fall in this category (Karakaya et al 2008;Kopp and Gillberg 1997).…”
Section: From a Psychiatric Perspectivementioning
confidence: 53%
“…Figures range from 0.03% in a large school-based sample of kindergarten, first-, second-, and third-grade students in Turkey (Karakaya et al 2008), 0.71% in kindergarten, first, second graders in the United States (Bergman, Piacentini, and McCracken 2002) to 1.9% in second graders in Finland (Kumpulainen et al 1998). The age groups studied vary between samples.…”
Section: From a Psychiatric Perspectivementioning
confidence: 99%